PENGARUH KOMPETENSI, PENGALAMAN, PROFESIONALISME DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT PADA KAP KOTA MAKASSAR - Patima, Patima (STIEM BONGAYA, 2019)
This research conducted with the aim of (1) Knowing and anlyzing the influence ofcompetencies on audit quality, (2) knowing and anlyzing the influence of work experience on auditquality, (3) knowing and analyzing the influence profesionalism on audit quality, (4) knowing andanalyzing the influence of auditor ethics on audit quality. Research uses primary data through asurvey of auditors working in the Public Accounting Firm of the Makassar city, amounting to 36people. The study was conducted for theree months from january to march 2019 Data was analyzedusing the Statistical Package for the Social Scienes (SPSS).The results of the study show that (1)Competance has a positive and significant effect on audit quality, (2) Experience has a positive andsignificant effect on audit quality, (3) Profesionalism has a positive and significant effect on auditquality, (4) Auditors’ ethics have no effect on audit quality.